Pharmacogenetic efficacy of perindopril in children and adolescents with type 1 diabetes mellitus in prediction of diabetic nephropathy - Rakhimova, Gulnara; Sadykova, Akida; Alimova, Nasiba (Medical and Health Science Journal, 2013)
DD genotype of ACE gene is a predisposing factor for chronic kidney disease terminating nephrotic syndrome in children with type 1 diabetes mellitus, while ACE gene II genotype upon diabetic nephropathy appears to be a protective one. The work was initiated to assess efficacy of perindopril in normoalbuminuric patients with type 1 diabetes mellitus by ACE genotype in the primary intervention of diabetic nephropathy. 22 normoalbuminuric patients with type 1 diabetes mellitus aged from 12 to 70 with diabetic nephropathy duration of 10 and more years were examined to be divided into two groups by ACE polymorphism including eleven-by-eleven carriers of II genotype and DD genotype, respectively. Perindopril in low doses is recommended to treat normoalbuminuric children and adolescents for optimization of intervention and therapy of diabetic nephropathy.
Keywords: Diabetic Nephropathies; inhibitory ACE; Angiotensin-Converting Enzyme Inhibitors; genotyp; diabetické nefropatie; Genotype; diabetes mellitus 1. typu; mladiství; výsledek terapie; mužské pohlaví; dítě; Child; antihypertenziva; Diabetes Mellitus, Type 1; Antihypertensive Agents; ženské pohlaví; Humans; ledviny; Kidney; Female; Adolescent; Treatment Outcome; lidé; Male